Engineered small extracellular vesicles for targeted delivery of perlecan to stabilise the blood–spinal cord barrier after spinal cord injury - Wei Peng; Wentao Zhang; Wei Cui; Wenjin Chen; Yin Zhuang; Rupeng Chu; Jinghua Tan; Jingbo Xue; Yiguo Yan; Guoyong Yin; Shujun Zhang; Yong Xie (Clinical and Translational Medicine)
Abstract Background Destruction of the blood–spinal cord barrier (BSCB) following spinal cord injury (SCI) can result in various harmful cytokines, neutrophils, and macrophages infiltrating into the injured site, causing secondary damage. Growing evidence shows that M2 macrophages and their small extracellular vesicles (sEVs) contribute to tissue repair in various diseases. Methods and Results In our previous proteomics‐based analysis of protein expression profiles in M2 macrophages and their sEVs (M2‐sEVs), the proteoglycan perlecan, encoded by HSPG2, was found to be upregulated in M2‐sEVs. Perlecan is a crucial component of basement membranes, playing a vital role in stabilising BSCB homeostasis and functions through its interactions with other matrix components, growth factors, and receptors. Here, we verified the high levels and remarkable therapeutic effect of M2‐sEV‐derived perlecan on the permeability of spinal cord microvascular endothelial cells exposed to oxygen glucose deprivation and reoxygenation in vitro. We also decorated the surface of M2‐sEVs with a fusion protein comprising the N‐terminus of Lamp2 and arginine glycine aspartic acid (RGD) peptides, which have an affinity for integrin αvβ3 and are primarily present on neovascular endothelium surfaces. In SCI model mice, these RGD‐M2‐sEVs accumulated at injured sites, promoting BSCB restoration. Finally, we identified M2‐sEV‐derived perlecan as a key player in regulating BSCB integrity and functional recovery post‐SCI. Conclusion Our results indicate that RGD‐M2‐sEVs promote BSCB restoration by transporting perlecan to neovascular endothelial cells, representing a potential strategy for SCI treatment. Key points Perlecan, a crucial component of basement membranes that plays a vital role in stabilising BSCB homeostasis and functions, was found to be upregulated in M2‐sEVs. M2‐sEVs decorated with RGD peptide can effectively target the neovascular endothelium surfaces at the injured spinal cord site. RGD‐M2‐sEVs promote BSCB restoration by transporting perlecan to neovascular endothelial cells, representing a potential strategy for SCI treatment.